Legal Position of Polish Competition Regulatory Authorities - Jakub MROŻEK (Communications of International Proceedings, 2021)
The article describes the legal position of the President of the Office of Competition and Consumer Protection in Poland (President of OCCP) – a government administration body responsible for regulating competition and consumer protection. The publication refers to the most important provisions of the Constitution of the Republic of Poland, which allow to fully recreate the legal position of this body. Initially, the position of the President of OCCP was described in comparison to other government administration bodies in Poland.  Further sections of the article describe the sui generis appeal procedure against the decisions of the President of OCCP. This procedure differs significantly from the “classical” appeal model outlined by the Constitution of the Republic of Poland. This model - referred to as “hybrid”, affects the special legal position of the President of OCCP.
Keywords: Competition; Consumers; Competition and consumer protection authorities; Poland; Constitution of the Republic of Poland.